(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
The main purpose of the research study, the fact that management of financial activity is apparent reliability, simplicity and precision of the integration processes in the accounting system. In the article the new approach, which aims neoinstitutsional economy, evolutionary approach to the financial information and information theory, so that we can learn about the center of the enterprise information integration processes, which can give a good description of the development of new approaches, their features as an automated accounting system and the development of effective integration into the modern-looking forms of generalization and introduction of emission methods. The main feature of this study is to characterize new approaches to economic information and the theory of evolution, which is an information and financial integration processes at the center of a campaign of corporate information.